Hallazgos histopatológicos en tracto reproductivo en conejas sometidas a ovariohisterectomía en la clínica pet company ubicada en la ciudad de Bogotá D.C. (2020)
Reproductive diseases in pet rabbits have been reported frequently in daily veterinary practice, and little information is available on their histopathological changes for more accurate diagnosis and prompt treatment. This study was carried out in order to contribute to the understanding of the development of these diseases and the presentation characteristics based on the histopathological findings; as well as analyzing the frequency of presentation of these making their relationship with literature. Female rabbits (Oryctolagus cuniculus) were taken from the Pet Company clinic who came to the clinic for reproductive problems with signs such as vulvovaginal bleeding, behavioral changes, vulvar hyperemia, among others, and we worked under a descriptive cross-sectional study, with a non-probabilistic, subjective sampling by reasoned decision. Endometrial hyperplasia, uterine adenocarcinoma and uterine inflammation are common disorders of this species, and in this study different microscopic and macroscopic findings were observed that are compatible with these diseases, which although they can also be observed in endometrial venous aneurysm and hydrometer. The average age of presentation for reproductive diseases in female rabbits was identified to be between 2 and 5 years, compared to several studies in which the average age of presentation of reproductive tract diseases is between 1 to 5 years. The Belier breed was the breed that presented the most pathologies confirming its relative susceptibility to the development of diseases.